2018
DOI: 10.1002/jctb.5673
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption/desorption characteristics, separation and purification of phenazine‐1‐carboxylic acid from fermentation extract by macroporous adsorbing resins

Abstract: BACKGROUND Pseudomonas chlororaphis GP72 is a biocontrol strain with great capacity to produce a wide range of secondary metabolites including phenazine derivatives. Phenazine‐1‐carboxylic acid (PCA) is an environmentally friendly antibiotic with broad‐spectrum biological and pharmaceutical activities. Many studies have been focused on engineering high‐yielding strains and optimizing fermentation bioprocesses to enhance PCA biosynthesis. However, the separation and purification of PCA in biotechnological prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…HPD-100B is a nonpolar resin (Table 1), and the two targeted components are low polarity compounds. is is consistent with the results of Bilal et al [33], who reported that nonpolar compounds could easily be adsorbed by nonpolar resins. Compared with syringoside, oleuropein has less polarity.…”
Section: Screening Of the Macroporous Resinsupporting
confidence: 93%
“…HPD-100B is a nonpolar resin (Table 1), and the two targeted components are low polarity compounds. is is consistent with the results of Bilal et al [33], who reported that nonpolar compounds could easily be adsorbed by nonpolar resins. Compared with syringoside, oleuropein has less polarity.…”
Section: Screening Of the Macroporous Resinsupporting
confidence: 93%
“…Organic solvents such as ethyl acetate, dichloromethane, chloroform, methylene dichloride, toluene, or diethyl ether are the most reported for this step of the purification process. Then, the organic phase where phenazines are dissolved can be evaporated and the dry solids dissolved in acetonitrile or methanol [ 19 , 20 , 22 , 23 , 27 , 29 , 32 , 52 , 68 , 69 , 70 ]. Some authors, after solvent utilization, include a chromatography step with silica gel to enhance the purification [ 29 , 71 , 72 , 73 , 74 ].…”
Section: Extraction and Purification Of Phenazinesmentioning
confidence: 99%
“…The separation and purification are mostly reported by thin layer chromatography (TLC) and preparative high-performance liquid chromatography (HPLC) which have good separation resolutions [ 68 , 71 , 75 , 76 , 77 ]. However, other techniques are being studied, such as capillary electrophoresis, free flow electrophoresis, and the use of microporous adsorbent resins as alternatives to reduce the price, the use of organic solvents and the time required for the separation [ 68 , 70 , 78 , 79 , 80 ]. Liu et al [ 78 ] applied capillary zone electrophoresis to separate and quantify PCA and 2-OH-PHZ from the culture broth of P. chlororaphis GP72, after an extraction step, offering a rapid and sensitive detection.…”
Section: Extraction and Purification Of Phenazinesmentioning
confidence: 99%
“…The 50 % taxadiene repartition between biomass and resin beads provides an important piece of information, as it showcases where the taxadiene that is being detected in the system is being captured. To our knowledge, this information has not been commonly reported as the extraction is generally made to the biomass and resin in conjunction [16,29,46] or to the single beads without biomass [17,47]. These results could have an important impact into determining the capacity of the resin beads to relieve the cells from intracellular toxicity of selected NP among other phenomena.…”
Section: Synergic Effect Of Hp-20 Resin Beads and Selected Solvent To Improve Taxadiene Extractionmentioning
confidence: 99%